(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
The objective of this document is to provide information regarding the innovative product, with focus on product differentiation providing a unique product like our product "Rainbow fries" which are not offered by other food stall in the area. This is a snack type product which is new and affordable to the customer which consists of healthy ingredients and combination of other products that gives satisfaction to the customers. The researchers decided to come up with this healthy and safe Rainbow Fries that will surely be enjoyed not only by other customers but also by health conscious people craving for salty but healthy food. The Survey method is the technique used to gather the data by asking questions to people who are thought to have desired information. The medium used is the Survey questionnaire. The researchers used the survey method because it is useful in describing the characteristics of a large population. Our business is feasible based on our product that we carry, the total layout and the minimal investment needed. Based on our survey 83% of respondents strongly agreed to our product while the rest of respondents are not satisfied which got the lowest percentage with 27%. The researchers made this product proposal to introduce a new innovation for the consumers which will give them a much healthier and enjoyable food for both adults and young individuals. The product contains special varieties of flavors that a typical fries sold nowadays does not have. Rainbow fries contains different colors that representing a rainbow which can be more attractable for the consumers. Aside from this, we also added in our stall another choices of food which are sandwiches and beverages. According to Samantha Ferchaw (December 1 2010) who study “The French fry: Staple of American Fast Food” in the United States, fast food has become the number one convenient source of food for many people. Not all the people eat this food, but people eat this food excessively, sometimes twice or three times a day. Back in the early 1900s, restaurants that sold hamburgers did not have anything to go along with it. Instead of eating baked or mashed potatoes, salads, or cooked vegetables, we are eating French fries with our meals. This study will help for the Future researchers in doing the study, the researchers help to continue the study and give them an idea to help them for building a new establishment.